2021
DOI: 10.1186/s12967-021-02743-3
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram to predict the high-risk RS in HR+/HER2-breast cancer patients older than 50 years of age

Abstract: Background The 21-gene recurrence score (RS) testing can predict the prognosis for luminal breast cancer patients. Meanwhile, patients > 50 years with RS > 25 have improved survival with adjuvant chemotherapy. The current study aimed to develop a nomogram with routine parameters to predict RS. Methods We included patients diagnosed with hormone receptor (HR)-positive, human epidermal growth factor receptor-2 (HER2)-negative who underwent the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Interestingly, there were no signi cant differences in all the included imaging features of ultrasound and mammogram between 70-GS high vs low risk patients (Table 1). Not surprisingly, the most 'classic' clincopathological parameters associated with 70-GS risk were still histological grade, PR and Ki-67 index (Table 1, Figure 2, 4), which was in accordance with studies building nomogram predicting 21-gene RS [17,29,30]. Majority (71.3%) of patients were clinical high risk according to AOL model.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, there were no signi cant differences in all the included imaging features of ultrasound and mammogram between 70-GS high vs low risk patients (Table 1). Not surprisingly, the most 'classic' clincopathological parameters associated with 70-GS risk were still histological grade, PR and Ki-67 index (Table 1, Figure 2, 4), which was in accordance with studies building nomogram predicting 21-gene RS [17,29,30]. Majority (71.3%) of patients were clinical high risk according to AOL model.…”
Section: Discussionsupporting
confidence: 83%
“…Study showed that the prognostic and predictive value of the 21-gene RS was consistent in different countries [27], however, there might be difference in the 21-gene assay performance across racial groups with better performance among white compared with African American and Hispanic individuals. [28] The 21-gene RS could be predicted by nomograms and machine-learning models based on clinicopathological parameters [29][30][31][32]. The 70-GS further strati es HR+/Her2-BC patients with clinically high-risk according to AOL model into binary (high vs low) or quartile categorized (ultra-high, high, low and ultra-low) risk classi cations [6,33].…”
Section: Discussionmentioning
confidence: 99%
“…In our multivariable analysis, a combination of menopause status, tumor grade, ER score, and PgR score independently predicted RS (accuracy: 0.800, 95% CI: 0.719–0.866) and RS > 25, respectively (accuracy: 0.858, 95% CI: 0.764–0.889). These results have been consistently observed in the previous studies which have built nomograms predictive of RS [ 42 , 50 , 51 , 56 , 57 ] and are unsurprising, as gene expression levels of ER and PgR were included in the algorithm designed by Paik et al when creating the 21-gene expression assay [ 1 ]. Moreover, menopause status independently predicted RS, an unanticipated result which is less well-described in previous studies [ 22 , 24 ].…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, data from the aforementioned study suggests that LVI has potential to serve as a surrogate biomarker of RS predictive of patients with luminal A disease who may benefit from adjuvant chemotherapy prescription. Similarly, Lee et al describe Ki-67 indices as predictive correlates of RS in their nomogram, with results validated by other authors in two more recent studies which developed surrogate nomograms to RS [50,51]. This is an unsurprising finding; within the 21-gene expression assay, comparison between the 16 cancer-related and 5 reference (or "housekeeping") genes is included in an algorithm to generate the RS [1].…”
Section: Discussionmentioning
confidence: 84%
“…Study showed that the prognostic and predictive value of the 21-gene RS was consistent in different countries [27], however, there might be difference in the 21-gene assay performance across racial groups with better performance among white compared with African American and Hispanic individuals. [28] The 21-gene RS could be predicted by nomograms and machine-learning models based on clinicopathological parameters [29][30][31][32]. The 70-GS further stratifies HR + / Her2− BC patients with clinically high-risk according to AOL model into binary (high vs low) or quartile categorized (ultra-high, high, low and ultra-low) risk classifications [6,33].…”
Section: Discussionmentioning
confidence: 99%